2010
DOI: 10.1021/jp100114v
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Characterization of the Inorganic−Bioorganic Interface by Solid State NMR: Alanine on a Silica Surface, a Case Study

Abstract: The molecular interface between bioorganics and inorganics plays a key role in diverse scientific and technological research areas including nanoelectronics, biomimetics, biomineralization, and medical applications such as drug delivery systems and implant coatings. However, the physical/chemical basis of recognition of inorganic surfaces by biomolecules remains unclear. The molecular level elucidation of specific interfacial interactions and the structural and dynamical state of the surface bound molecules is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(105 citation statements)
references
References 61 publications
5
100
0
Order By: Relevance
“…In spite of this, the application of solid-state NMR to understand biomolecules adsorption on silica is recent. 211,[224][225][226][227][228] This is due to the low intrinsic sensitivity of the 13 C nucleus. In conjunction with the fact that the biomolecule is a minority species in the samples, it causes NMR signals to be very weak, so that long accumulation times are necessary -unless one uses expensive isotopically enriched biomolecules.…”
Section: Nmr Techniquesmentioning
confidence: 99%
“…In spite of this, the application of solid-state NMR to understand biomolecules adsorption on silica is recent. 211,[224][225][226][227][228] This is due to the low intrinsic sensitivity of the 13 C nucleus. In conjunction with the fact that the biomolecule is a minority species in the samples, it causes NMR signals to be very weak, so that long accumulation times are necessary -unless one uses expensive isotopically enriched biomolecules.…”
Section: Nmr Techniquesmentioning
confidence: 99%
“…In that sense, solid-state NMR is a perfect tool of investigation for the hybrid organic−inorganic interfaces in nanomaterials. NMR spectroscopy and more particularly dipolar recoupling experiments were used recently to identify interacting moieties in alanine adsorbed on a mesoporous silica SBA-15 surface, 7 and later in glycine adsorbed on the same support. 8 In both cases, the authors show that the ammonium group interacts directly with silanols (predominantly terminal ones) on the surface while the carboxylates seem to freely reorient.…”
Section: Introductionmentioning
confidence: 99%
“…In the complementary works by Amitay‐Rosen97 and Ben Shir et al. ,98 the behavior of selectively labeled alanine inside mesoporous SBA‐15 or MCM‐41 was probed by means of 1 H and 2 H MAS NMR. Ben Shir et al.…”
Section: Amino Acids and Peptides In Confinement For Medical Applicmentioning
confidence: 99%
“…Ben Shir et al. 98 were able to detect a single population of surface‐bound alanine at a hydration state lower than four protons per nm 2 . It was found that the binding occurs between three adjacent silanol binding sites with a distance r[N⋅⋅⋅Si]=4.0–4.2 Å.…”
Section: Amino Acids and Peptides In Confinement For Medical Applicmentioning
confidence: 99%
See 1 more Smart Citation